Gene Biomarkers in Congenital Hyperinsulinism: Life Sciences-Endocrine - Valizadeh, Reza; Seidkhani, Hossein; Mohebinejad, Zahra; Kavarizadeh, Forouzan; Arefipour, Abbass (International Journal of Life Science and Pharma Research, 2024)
Congenital hyperinsulinism (CHI) is a rare type of disease that causes a severe drop in blood sugar in infants. This diseaseprevents reaching enough sugar to the child’s brain and causes lifelong and permanent damage. This study aims to investigate genebiomarkers in congenital hyperinsulinism. In this study, after reviewing the texts and searching for the bioinformatics databases of NCBI,Genecards, Swiss-prot, Diseasome, etc., the genes involved in the disease based on at least one of the methods in-vivo, in-vitro, and insilicohas been extracted as candidate genes. The expression data obtained from each group was standardized compared to the controlgroup to compare the results in case and control groups. Then, the connection network of expression data of candidate genes in patientsand healthy people were drawn separately with the help of MATLAB software (Version 9.1), and the correctness of these networks anddetermined biomarkers were checked using the rectome and diseasome database. All statistical calculations were done using R and Matlabsoftware. In the present study, the essential genes of CHI disease were identified using 5 central criteria, including maximum neighborhoodcomponent, degree, closeness, radiality, and betweeness. Based on the results of the central criteria method, INS-PRKACA-PRKACBPRKACG-AKT1 genes had the most repetitions. According to the identification of the most effective genes related to CHI disease in thepresent study, it is suggested that further studies need to be designed at the in vitro and clinical levels on the identified effective genes asdiagnostic biomarkers of CHI disease.